Nuclear transfer alters placental gene expression and associated histone modifications of the placental-specific imprinted gene pleckstrin homology-like domain, family A, member 2 (PHLDA2) in cattle - Arnold, Daniel R. [UNESP]; Gaspar, Roberta C. [UNESP]; Rocha, Carlos V. da [UNESP]; Sangalli, Juliano R.; Bem, Tiago H. C. de; Correa, Carolina A. P. [UNESP]; Penteado, Joao C. T. [UNESP]; Meirelles, Flavio V.; Lopes, Flavia L. [UNESP] (Csiro Publishing, 2017)
Abnormal placental development is frequent in nuclear transfer (NT) pregnancies and is likely to be associated with altered epigenetic reprogramming. In the present study, fetal and placental measurements were taken on Day 60 of gestation in cows with pregnancies produced by AI, IVF and NT. Placentas were collected and subjected to histological evaluation, the expression of genes important in trophoblast differentiation and expression of the placental imprinted gene pleckstrin homology-like domain, family A, member 2 (PHLDA2), as well as chromatin immunoprecipitation (ChIP) for histone marks within the promoter of PHLDA2. Fewer binucleated cells were observed in NT cotyledons, followed by IVF and AI cotyledons (P<0.05). Expression of heart and neural crest derivatives expressed 1 (HAND1), placental lactogen (PL), pregnancy-associated glycoprotein 9 (PAG-9) and PHLDA2 was elevated in NT cotyledons compared with AI cotyledons. Expression of PHLDA2 was higher in IVF than AI samples (P<0.05). ChIP revealed an increase in the permissive mark dimethylation of lysine 4 on histone H3 (H3K4me2), surprisingly associated with the silent allele of PHLDA2, and a decrease in the inhibitory mark H3K9me2 in NT samples. Thus, genes critical for placental development were altered in NT placentas, including an imprinted gene. Allele-specific changes in the permissive histone mark in the PHLDA2 promoter indicate misregulation of imprinting in clones. Abnormal trophoblast differentiation could have resulted in lower numbers of binucleated cells following NT. These results suggest that the altered expression of imprinted genes associated with NT are also caused by changes in histone modifications.
Keywords: assisted reproductive technologies; bovine; cotyledons; H3K4me2; H3K9me2; mRNA